SUPEROXIDE DISMUTASE ACTIVITY AND ETHANOL RESPIRATION IN A FUNGI RESISTANCE TO ETHANOL MONASCUS SP. MM - Julistiono, Heddy; Suharna, Nandang; Desnora, Beni (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTMonascus sp. MM was a contaminant fungus isolated from museum specimenpreserved with ethanol 70 %. In order to verify role of superoxide dismutase (SOD) inprotecting cell from ethanol toxicity during ethanol metabolism, SOD activities of Monascussp.MM and a Monmcus sp. NGK, which was isolated fiom fermented red rice (angkak), werecompared. When fungus was grown with glucose, CuIZn-SOD activity of Monascus sp., MMwas 7.1 times of thht of Monascus sp. NGK. Whereas in ethanol medium, CuIZn-SOD activityof Monarcus sp. MM was 24.6 times of that in Monascus sp. NGK. Induction of CuIZn-SODMonmcus sp. MM by ethanol was not observed. Compared with Mn-SOD, activity of CuIZn-SOD was markedly important (I 0 times of Mn-SOD when fungi grown with ethanol; 12 timeswhen the fungi grown with glucose). The data indicated that Cu/Zn-SOD might play animportant role in protecting cell fiom ethanol toxicity during ethanol metabolism. Ethanolrespiration rate of Monascus sp. MM was also important since O2 consumption and ethanoldegradation rates were clearly higher than that of Monascus sp. NGK.Keywords: Monarcw sp., superoxide dismutase, respiration, ethanol resistance.